DAURU AL-KITAB AL-‘ARABIYAH BAINA YADAI AULADINA FI ITSROI AL-MUFRODAT LADA AL-ATHFAL AL-INDUNISIYIN: دور كتاب العربية بين يدي أولادنا في إثراء المفردات العربية لدى الأطفال الإندونيسيين - Siti Mufarokah; Saadiyah Ratnasari Sagala; Neng Silvia; Zuhdina Gazali (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study aims to describe the curriculum for teaching the book "Al-Arabiyah Baina Yadaia Awladina" at Ar-Raayah Islamic Elementary School in Sukabumi, and to analyze in depth the role of this book in enriching Arabic vocabulary (mufradat) among Indonesian children at the school. The study adopted a descriptive-analytical qualitative approach utilizing a field study design. Data were gathered through a "data triangulation" strategy encompassing semi-structured interviews with the first-grade Arabic teacher, direct classroom observations, questionnaires distributed to parents, and an analysis of official academic records of students' performance over a six-month period. The data underwent processing through three systematic steps: data condensation, data display, and conclusion drawing. The findings revealed that Ar-Raayah Islamic Elementary School intensively relies on this series with an integration rate of up to 80% through the application of the "Communicative Approach." The most prominent factors contributing to the success of this experience included the attractive visual design of the book, the deployment of game-based learning and role-playing strategies, and the transition of the teacher's role into a facilitator who creates an immersive linguistic environment. The tangible impact of the curriculum was demonstrated by a significant leap in language acquisition, with students acquiring between 40 to 80 vocabulary words within a single semester. Furthermore, official evaluations showed that 57% of the students achieved a "Good" level of language proficiency, alongside an increase in self-confidence and the ability to engage in direct functional communication without resorting to mental translation.